Temas transversais em texto dissertativo - argumentativo: uma experiência a partir do uso das NTDIC - Silva, Edineide de Santana Cardoso da (2015)
In this final conclusion presented to the postgraduate studies in Languages Professional Network Program (PROFLETRAS), we intend to show search results in terms of theory and practice involving the production of dissertative-argumentative text using transversal themes (TT). The most purpose was to prove that the pedagogical support of New Information and Communication Digital Technologies (NTDIC) occurs in a very positive way. This is proved from our research goal: to compare the students’ production of dissertative-argumentative text before and after they use such tools as facilitators means of textual production, in terms of content. To execute our project, we use the internet as search source of information and knowledge of Transversal themes discussed in class. The idea was to enrich the field of information and knowledge of the students through reading, discussion and production of texts. The subjects of our research were students from Public School Governor Albano Franco, a school in the city of Aracaju, Sergipe.